Hemolytic Disease of the New-born Due to Anti-c Isoimmunization: A Case Report (Indian Journal of Applied-Basic Medical Sciences, 2021)
Introduction: The Rhesus (Rh) blood group system is one of the complex blood group systems in humans. The Rh system  plays important role in transfusion and clinical applications. The Rh antibodies are being the main cause of Hemolytic Disease of Newborn (HDN). Anti-D is the most common cause of severe HDN [1], but it does not  mean other Rh antibodies won’t cause HDN. The second common cause of severe HDN is Anti-cantibodies [2]  which might miss during the routine screening of antenatal patients. Here we are discussing a case of HDN  caused by Anti-c antibody isoimmunization. The relative ability of antigen to cause clinically significant HDN  has been the focus of debate [3]. Material and Method: The blood grouping was done for both mother and newborn in QWALYS 3 (DIAGAST) and confirmed with  gold standard test tube method. Direct and Indirect Antiglobulin Test was done with polyspecific column  agglutination card (BIORAD). The Antibody screening was done with 3- cell panel (BIORAD) and Antibody  identification was done with 11-cell panel (BIORAD). Results: The blood group of mothers is “O” positive and the blood group of newborns is confirmed as “O” positive. The  newborn got DAT Grade 4 positive. The mother sample is tested for IAT which gave Grade 3 positive. The  antibody screening shows positive and antibody identification shows the presence of Anti-c antibody in the  mother’s serum. Discussion:The newborn had severe hemolytic anemia in which the cause was found to be Anti-c antibody. Though the  antibody is severe next to Anti- D, still it produces very severe hemolytic disease. Among all severe HDN Anti c antibodies cause 8.5% of cases [5]. Conclusion: The newborn is treated with double volume exchange transfusion with same blood group [5] and discharged  after 10 days. The case report shows the importance of implementation of protocols for screening irregular  antibodies to avoid perinatal mortality.
Keywords: Hemolytic Disease; New-born; Anti-c Isoimmunization; Isoimmunization; Case Report